Network-Based Transcranial Direct Current Stimulation May Modulate Gait Variability in Young Healthy Adults - Zhou, Rong; Zhou, Junhong; Xiao, Yanwen; Bi, Jiawei; Biagi, Maria Chiara; Ruffini, Giulio; Gouskova, Natalia A.; Manor, Brad; Liu, Yu; Lü, Jiaojiao; Lo, On-Yee (Frontiers in Human Neuroscience, 2022)
Purpose: Previous studies have linked gait variability to resting-state functional connectivity between the dorsal attention network (DAN) and the default network (DN) in the brain. The purpose of this study was to examine the effects of a novel transcranial direct current stimulation (tDCS) paradigm designed to simultaneously facilitate the excitability of the DAN and suppress the excitability of the DN (i.e., DAN+/DN- tDCS) on gait variability and other gait characteristics in young healthy adults. Methods: In this double-blinded randomized and sham-controlled study, 48 healthy adults aged 22±2 years received one 20-minute session of DAN+/DN- tDCS (n=24) or no stimulation (the Sham group, n=24). Immediately before and after stimulation, participants completed a gait assessment under three conditions: walking at self-selected speed (i.e., normal walking), walking as fast as possible (i.e., fast walking), and walking while counting backward (i.e., dual-task walking). Primary outcomes included gait stride time variability and gait stride length variability in normal walking conditions. Secondary outcomes include gait stride time and length variability in fast and dual-task conditions, and other gait metrics derived from the three walking conditions. Results: Compared to the Sham group, DAN+/DN- tDCS reduced stride length variability in normal and fast walking conditions, double-limb support time variability in fast and dual-task walking conditions, and step width variability in fast walking conditions. In contrast, DAN+/DN- tDCS did not alter average gait speed or the average value of any other gait metrics as compared to the sham group. Conclusion: In healthy young adults, a single exposure to tDCS designed to simultaneously modulate DAN and DN excitability reduced gait variability, yet did not alter gait speed or other average gait metrics, when tested just after stimulation. These results suggest that gait variability may be uniquely regulated by these spatially-distinct yet functionally-connected cortical networks. These results warrant additional research on the short- and longer-term effects of this type of network-based tDCS on the cortical control of walking in younger and older populations.